Utopia's garden : French natural history from Old Regime to Revolution - Spary, E. C. (Emma C.) (University of Chicago Press, 2000)
The royal Parisian botanical garden, the Jardin du Roi, was a jewel in the crown of the French Old Regime, praised by both rulers and scientific practitioners. Yet unlike many such institutions, the Jardin not only survived the French Revolution but by 1800 had become the world's leading public establishment of natural history: the Muséum d'Histoire Naturelle. E.C. Spary traces the scientific, administrative, and political strategies that enabled the foundation of the Muséum, arguing that agriculture and animal breeding rank alongside classification and collections in explaining why natural history was important for French rulers.